(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article presents studies related to the reduction of stress concentration acting on prismatic specimen subject to axial loading. Using ANSYS software, a topological optimization was performed which aims to reduce the stresses in the endangered areas. The aim of identification of the geometric parameters accomplished after the completion of topological optimization of the objective function is to minimize the stresses in the engaged areas. An analysis performed were to show the influence of stresses acting on the fatigue limit during different cycles. The results of the study were present in a graphical form.